Analysis of m6A modification regulators in the substantia nigra and striatum of MPTP-induced Parkinson's disease mice. (20th November 2022) - Yu, Ziying; Huang, Lishuang; Xia, Yinyin; Cheng, Shuqun; Yang, Cantao; Chen, Chengzhi; Zou, Zhen; Wang, Xiaoliang; Tian, Xin; Jiang, Xuejun; Zhou, Lixiao
Highlights: Expression of m6A regulators was aberrant in the PD mice. The altered m6A regulators were found both in the substantia nigra and striatum. The change of m6A regulators is related to abnormal behavior in mice. Abstract: Parkinson's disease (PD) is one of the most common neurodegenerative disorders of aging that impairs predominately dopaminergic neurons. N6-methyladenosine (m6A) is the most prevalent form of internal RNA modification in eukaryotes and it plays an essential role in normal brain development and neurodegenerative diseases. The m6A status is dynamically modulated by diverse types of genes called "writers", "erasers" and "readers". However, whether these m6A regulators are perturbed in PD remains poorly understood. To clarify this point, we established a PD mouse model using 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP). The motor as well as learning and memory ability of mice were evaluated through and rotarod and Y maze spontaneous alternation tests. Morphological characteristics of tyrosine hydroxylase (TH)-positive cells were visualized using immunohistochemistry, while expressions of alpha-synuclein (α-syn) and TH were determined by using western blot. Furthermore, the expressions of the m6A regulators in the substantia nigra and striatum were evaluated by using qRT-PCR and western blot. As a result, the MPTP-induced PD mice suffered from learning and memory as well as motor defects. Additionally, there were significant TH+ neuron losses in the substantia nigra and striatum of MPTP-injected mice. In the PD mice, proteins including ALKBH5, IGF2BP2 were up-regulated in the substantia nigra, while YTHDF1 and FMR1 was down-regulated. For the striatum, FMR1 and CBLL1 were up-regulated, while IGF2BP3, METTL3 and RBM15 were down-regulated. The expression of genes at the mRNA level were partially in accordance with the protein changes. These findings indicate the m6A regulators may participate in PD pathogenesis.